New digital anatomical data of Keichousaurus hui (Reptilia: Sauropterygia) and its phylogenetic implication - Jiayu Xu; Yu Guo; Yucong Ma; Wei Wang; Long Cheng; Fenglu Han (PeerJ)
Three complete skulls of Keichousaurus hui from the Middle Triassic Xingyi Fauna of southwestern China were examined using high-resolution computed tomography (CT) scanning. The CT images allow a few refinements and supplements in cranial anatomy. Some previously ambiguous anatomical characters were identified, including the presence of an L-shaped ectopterygoid that extends from the lateral side of the pterygoid and bends ventrally, the wedge-shaped posterolateral process of the frontal, the trapezoidal pterygoid for articulating with the palatine, and a rodlike basioccipital tuber that extends posterolaterally. These new features provide new detailed anatomical information for taxonomy. The new phylogenetic analysis of Sauropterygiformes places Keichousaurus as an eosauropterygian that is more basal than the monophyly which includes Nothosauridae and Pistosauroidea. Moreover, the result also suggests that Keichousaurus is more closely related to Chinese pachypleurosaurs-like eosauropterygians than to European pachypleurosaurs and more derived than other Chinese pachypleurosaurs-like forms.